Predictors of quality of life after moderate to severe traumatic brain injury - Weber, Karina Tavares; Guimarães, Viviane Assunção; Pontes, Octávio M, Neto; Leite, João P.; Takayanagui, Osvaldo Massaiti; Santos-Pontelli, Taiza E. G. (Arquivos de Neuro-Psiquiatria, 2016)
Objective To verify correlations between age, injury severity, length of stay (LOS), cognition, functional capacity and quality of life (QOL) six months after hospital discharge (HD) of victims of traumatic brain injury (TBI).Method 50 patients consecutively treated in a Brazilian emergency hospital were assessed at admission, HD and six months after HD. The assessment protocol consisted in Abbreviated Injury Scale, Injury Severity Score, Glasgow Coma Scale (GCS), Revised Trauma Score (RTS), Mini Mental Test, Barthel Index and World Health Organization QOL - Brief.Results Strong negative correlation was observed between LOS and GCS and LOS and RTS. An almost maximal correlation was found between RTS and GCS and functional capacity and GCS at HD. Age and LOS were considered independent predictors of QOL.Conclusion Age and LOS are independent predictors of QOL after moderate to severe TBI.
Keywords: brain injuries; epidemiology; quality of life